Patient Anxiety Levels Against Dental Health Services During the Covid-19 Pandemic Period at Meuraxa General Hospital Banda Aceh City - Mulfira firnanda; Sari, Kartika; wati, Hasnidar; Sulasmi; Jazaul Husna; Salfiyadi, Teuku (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2022)
Corona Virus or Coronavirus is a group of viruses that can cause disease in animals or humans. Various efforts must be carried out to realize optimal public health status, one of which is the implementation of health services. This study aims to get an overview of the level of anxiety of the people who seek treatment at the dental and oral clinic during the Covid-19 period at the Meuraxa General Hospital. The sample in this study was 50 people, and the community visited the dental clinic with the total sampling method. Place in the study at the Meuraxa General Hospital Banda Aceh City in 2022. The method in this study used analytical research with a cross-sectional design. The aim is to determine the effect of patient anxiety levels on dental clinic services during the COVID-19 pandemic at Meuraxa Hospital, Banda Aceh City. The results of this study indicate that women tend to experience greater anxiety than men. Respondents experienced anxiety about dental poly services during the COVID-19 pandemic in the severe category in as many as 23 people (46%), the moderate anxiety level category in as many as 19 people (38%), and only 8 people with mild anxiety level (16%). The majority of the samples stated that the dental poly service was good as many as 42 people (84%), while the sample that stated the dental poly service was lacking was only 8 people (16%). In conclusion, the level of patient anxiety about visits to dental and oral health services increased during the Covid-19 pandemic.